2013
DOI: 10.1111/mec.12295
|View full text |Cite
|
Sign up to set email alerts
|

Divergence in coloration and ecological speciation in the Anolis marmoratus species complex

Abstract: Adaptive divergence in coloration is expected to produce reproductive isolation in species that use colourful signals in mate choice and species recognition. Indeed, many adaptive radiations are characterized by differentiation in colourful signals, suggesting that divergent selection acting on coloration may be an important component of speciation. Populations in the Anolis marmoratus species complex from the Caribbean island of Guadeloupe display striking divergence in the colour and pattern of adult males t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 95 publications
(163 reference statements)
3
35
0
1
Order By: Relevance
“…Although neutral processes cannot be completely ruled out as causes of the positive relationship between speciation rate and TE density in Hox clusters, the fact that microsatellite repeats located in the Hox clusters did not accumulate with the number of speciation nodes, and showed the expected pattern from neutral evolution, argues against this. In addition, low effective population sizes are unlikely to apply to Caribbean Anolis lizards as they are characterized by generally high abundances [24] and estimates of historical effective population sizes suggest this has been the case throughout the lineage's history [76]. Environmental factors such as temperature or humidity can potentially promote TE activity as demonstrated in model organisms exposed to biotic and abiotic stressors [77][78][79].…”
Section: Discussionmentioning
confidence: 99%
“…Although neutral processes cannot be completely ruled out as causes of the positive relationship between speciation rate and TE density in Hox clusters, the fact that microsatellite repeats located in the Hox clusters did not accumulate with the number of speciation nodes, and showed the expected pattern from neutral evolution, argues against this. In addition, low effective population sizes are unlikely to apply to Caribbean Anolis lizards as they are characterized by generally high abundances [24] and estimates of historical effective population sizes suggest this has been the case throughout the lineage's history [76]. Environmental factors such as temperature or humidity can potentially promote TE activity as demonstrated in model organisms exposed to biotic and abiotic stressors [77][78][79].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found low genetic differentiation between distinct dewlap phenotypes (D'Angiolella et al, 2011;Lambert et al, 2013;Ng and Glor, 2011;Stapley et al, 2011). Within some anole taxa, divergence in sexual signals has not prevented high levels of contemporary gene flow between populations (Muñoz et al, 2013), which might also be the case of D. punctata and D. philopunctata.…”
Section: Genetic and Phenotypic Divergence Between D Punctata And Dmentioning
confidence: 97%
“…The degree of dewlap dissimilarity that disrupts species recognition and mating in dactyloids is unclear (Ng and Glor, 2011;Stapley et al, 2011). In addition to the dewlap, anoles rely on a range of visual signals, including body coloration and stereotyped head bobbing displays (Jenssen and Gladson, 1984;Losos, 1985;Macedonia and Stamps, 1994;Muñoz et al, 2013). Other studies have also found low genetic differentiation between distinct dewlap phenotypes (D'Angiolella et al, 2011;Lambert et al, 2013;Ng and Glor, 2011;Stapley et al, 2011).…”
Section: Genetic and Phenotypic Divergence Between D Punctata And Dmentioning
confidence: 99%
“…Environmental gradients are often viewed as one important driver of intraspecific adaptive variation that may allow species to persist through changing environments and be a source of variation for ecological speciation and intraspecific adaptive variation (51,79). In combination with environmental data layers from geographic information systems, genetic analyses of population structure and gene flow have provided insights into the role of ecological factors in promoting divergent selection and speciation in amphibians (77), phenotypic divergence in Anolis lizards (80), and convergent morphological evolution consistent with ecological speciation in three lizard species in the extreme White Sands desert of the southwestern United States (81). Morphologically similar but genetically distinct amphibian lineages sampled across climatic gradients have also shown that divergent selection maintains distinct lineage distributions in the salamander Aneides flavipunctatus/niger in western North America (82).…”
Section: Ecological Genetics and Ecological Gradientsmentioning
confidence: 99%